Inter- and Intra-Subunit Butanol/Isoflurane Sites of Action in the Human Glycine Receptor - McCracken, Mandy L.; Gorini, Giorgio; McCracken, Lindsay M.; Mayfield, R. Dayne; Harris, R. Adron; Trudell, James R. (Frontiers in Molecular Neuroscience, 2016)
Glycine receptors (GlyRs) mediate inhibitory neurotransmission and are targets for alcohols and anesthetics in brain. GlyR transmembrane (TM) domains contain critical residues for alcohol/anesthetic action: amino acid A288 in TM3 forms crosslinks with TM1 (I229) in the adjacent subunit as well as TM2 (S267) and TM4 (Y406, W407, I409, Y410) in the same subunit. We hypothesized that these residues may participate in intra-subunit and inter-subunit sites of alcohol/anesthetic action. The following double and triple mutants of GLRA1 cDNA (encoding human glycine receptor alpha 1 subunit) were injected into Xenopus laevis oocytes: I229C/A288C, I229C/A288C/C290S, A288C/Y406C, A288C/W407C, A288C/I409C, and A288C/Y410C along with the corresponding single mutants and wild-type GLRA1. Butanol (22 mM) or isoflurane (0.6 mM) potentiation of GlyR-mediated currents before and after application of the cysteine crosslinking agent HgCl2 (10 µM) was measured using two-electrode voltage clamp electrophysiology. Crosslinking nearly abolished butanol and isoflurane potentiation in the I229C/A288C and I229C/A288C/C290S mutants but had no effect in single mutants or wild-type. Crosslinking also inhibited butanol and isoflurane potentiation in the TM3-4 mutants (A288C/Y406C, A288C/W407C, A288C/I409C, A288C/Y410C) with no effect in single mutants or wild-type. We extracted proteins from oocytes expressing I229C/288C, A288C/Y410C, or wild-type GlyRs, used mass spectrometry to verify their expression and possible inter-subunit dimerization, plus immunoblotting to investigate the biochemical features of proposed crosslinks. Wild-type GlyR subunits measured about 50 kDa; after crosslinking, the dimeric/monomeric 100:50 kDa band ratio was significantly increased in I229C/288C but not A288C/Y410C mutants or wild-type, providing support for TM1-3 inter-subunit and TM3-4 intra-subunit crosslinking. A GlyR homology model based on the GluCl template provides further evidence for a multi-site model for alcohol/anesthetic interaction with human GLRA1.